Design and implementation of a cost-efficient clamping capacitor boost converter for a hybrid renewable energy system for increased gain to fulfil demands - KMD Riyaz Ali; W. Abitha Memala (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
Power generation plants are built in rural areas to meet the power demands and empower the financial status. The existing method of electrical power generation is difficult to meet the growing population as they are turning to hybrid renewable energy systems to meet the increasing demand. They were also not focused on power saving and flow with reduced power loss. The power generated from hybrid renewable energy systems is distributed to rural areas through a DC-DC converter. The DC-DC converter converts the Hybrid Renewable Energy System (HRE) output into a high DC voltage transmitted in a bus. The proposed HRE system consists of solar and wind plants in the network. So, for transferring, saving, and utilizing the power generated from the hybrid renewable energy system, a cost-efficient clamping capacitor boost converter (CCBC) with increased voltage gain is proposed. The CCBC has a clamping capacitor in-built with 2-diodes and 2-capacitors. The voltage gain produced using the proposed CCBC is doubled with the conventional converters. There is no high range of power spikes in the converter's capacitor. This paper explains the architecture and the complete functionality of the CCBC with the simulation results in detail. The simulation results conclude that the proposed CCBC provides cost-efficient high voltage gain converters for HRE systems, providing more than 500 W, which fulfills the demand of a single rural area.